Lion Motif used in Buddhist Architecture of Ancient Bangladesh - Islam, Sk. Zohirul (American International Journal of Social Science Research, 2018)
Lion is the king of the animal world. They live in the plains and grassy hills. The male lion’s job is to protect the clan from enemies. However, lions do not have any natural enemy. Due to these characteristics, the lion has been considered through all ages in the world as a symbol of royalty and protection as well as of wisdom and pride. In Buddhism, lions are symbolic of the Bodhisattvas. In Buddhist architecture, lion motifs or figure were used as protectors of Dharma and therefore support the throne of the Buddha’s and Bodhisattvas. The lion motifs (symbol) were also used at the entrance of the monasteries and shrines possibly for the same reason. In ancient Bangladesh, there are various types of Lion motif used in terracotta plaques of Ananda Vihara, Rupbhan Mura and Shalban Vihara at Mainamati in Comilla district, Vashu Vihara, Mankalir Kundo at Mahasthangarh in Bogra district and Somapura Mahavihara at Paharpur in Naogaon district. This paper aims to address the cultural significance of the lion motif in Buddhist architecture of ancient Bangladesh and relates it to various types of representation to understand its origin and evaluation.